2019
DOI: 10.1111/jpim.12504
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hybrid Organizations in Scaling Social Innovations in Bottom‐of‐the‐Pyramid Markets: Insights from Microfinance in India

Abstract: While social innovations that solve financial exclusion have gained increasing attention as a means of helping the poor in developing markets, little research has empirically investigated the types of organizations that drive these innovations to achieve scale. Hybrids, a type of organization that exist in between traditional organizational forms, are said to have rapidly gained prevalence, especially in bottom-of-the-pyramid markets. Some scholars claim that hybrids are largely responsible for the spread of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 70 publications
1
23
0
2
Order By: Relevance
“…In their article “The Role of Hybrid Organizations in Scaling Social Innovations in Bottom‐of‐the‐Pyramid Markets: Insights from Microfinance in India,” Vassallo, Banerjee, Prabhu, and Voola () examine three hybrid forms of organizations for social innovation. The authors empirically explore what types of hybrid organizational forms are more likely to achieve greater usage in bottom‐of‐the‐pyramid markets, especially given market heterogeneity relating to varying levels of development and social diversity.…”
Section: An Overview Of Contributions To This Jpim Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…In their article “The Role of Hybrid Organizations in Scaling Social Innovations in Bottom‐of‐the‐Pyramid Markets: Insights from Microfinance in India,” Vassallo, Banerjee, Prabhu, and Voola () examine three hybrid forms of organizations for social innovation. The authors empirically explore what types of hybrid organizational forms are more likely to achieve greater usage in bottom‐of‐the‐pyramid markets, especially given market heterogeneity relating to varying levels of development and social diversity.…”
Section: An Overview Of Contributions To This Jpim Special Issuementioning
confidence: 99%
“…How do these market actors balance the cost and benefits of social innovation efforts? While Vassallo et al () evaluate three types of organizations and show that each organizational form achieves greater usage under various conditions in India and Paparoidamis et al () focus on consumer responses to green products, if the cost to providers and users are taken into consideration, would their results be different? ‐Though all articles in this special issue identify the complexities of social innovation and the corresponding high effort that is needed to implement it successfully, the implicit higher costs (in terms of time, human resources, organizing, etc.) are not measured.…”
Section: Where Next? Emerging Research Priorities In Social Innovationmentioning
confidence: 99%
“…Similarly, in a public policy setting, Sachs et al (2019) have identified six SDG transformations and associated priorities. Both studies recognize the strong interdependencies across the 17 SDGs (e.g., Vassallo et al, 2019). As marketing scholars embrace RRBM principles, their work can further progress on the SDGs.…”
Section: The Sdgs and The Future Of Marketingmentioning
confidence: 99%
“…Battilana and Lee (2014) drew on insights from three strands of literature and conceptualised hybridity as combinations of (a) organisational identities, (b) organisational forms, and (c) institutional logics. In recent years, much of the conceptual development around the notion of hybridity has drawn on social enterprises, which confront a vivid hybridity challengeto effectively combine their business-orientation and their charity-orientation (eg, Ebrahim et al, 2014;Litrico & Besharov, 2019;McMullen, 2018;Ramus & Vaccaro, 2017;Vassallo, Prabhu, Banerjee, & Voola, 2019). Battilana and Lee's (2014) review speaks largely to this body of work and focuses on hybridization that combines business-and charity-oriented actions.…”
Section: Hybriditymentioning
confidence: 99%